Menzalimi Diri Sendiri Dalam Al-Qur’an (Studi Penafsiran Ayat-Ayat Zhalim Li Nafsih Dalam Tafsir Al-Misbah) - Alirman; Sulthoni, Akhmad; Saputra , Akhmadiyah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
Tyranny is often known in society as a form of crime against others. Islam discusses zhalim in the Qur'an not only aimed at the perpetrators of crimes against others, but also at oneself. The Qur'an also mentions three groups of Allah's chosen ones as the inheritors of the book that will be put in heaven. One of the 3 verses in the verse is the group of zhalim li nafsih or tyranny of oneself, thus raising the question, how to interpret the verses of zhalim li nafsih, so that the zhalim is also sometimes interpreted as including the inhabitants of heaven. So the author is interested in discussing the interpretation of zhalim li nafsih in Tafsir Al-Misbah as a contemporary book of tafsir. This research aims to find out the meaning of zhalim li nafsih in the Qur'an based on the perspective of Tafsir Al-Misbah, as well as its implementation in life applications. The results of this study are zhalim li nafsih according to M.Quraish Shihab are people who mistreat themselves due to arrogance, disbelief, arrogance, committing many sins and mistakes or lack of charity and its implementation contains the urgency to stay away from self-tyranny and continue to try to be better in living life.